Ballistic response of hexagonal boron nitride monolayer under impact of a nano-projectile. (June 2019) - Tian, Hong; Zhang, Bin; Li, Q.M.
Highlights: A finite element model is developed for h -BN monolayer target, where the BN bonds are represented by Timoshenko beam elements. The elastic properties and bond strength of h -BN monolayer and graphene are verified by nano-indentation simulations. The ballistic response of h -BN monolayer is dependent of the impact speed of the projectile. The stress and deformation wave propagations in the h -BN monolayer interact with the movement of projectile and the material bond failure. H -BN material has potential to increase the ballistic performance significantly for armor application. Abstract: The response of a hexagonal boron nitride ( h -BN) monolayer subjected to ballistic impact is studied using an explicit finite element (FE) model based on molecular structural mechanics where BN bonds are represented by the nonlinear Timoshenko beam elements. The elastic properties and bond strength of h -BN monolayer and graphene are verified by nano-indentation using FE and molecular dynamics simulations. It shows that the ballistic response of h -BN monolayer is dependent of the impact speed of the projectile. The stress and deformation wave propagations in the h -BN monolayer interact with the movement of projectile and the material bond failure, which, in turn, influence the ballistic performance of the h -BN monolayer target. It shows that h -BN material, in comparison with conventional armor materials, has potential to increase the ballistic performance significantly if it could be practically made for armor application. Graphical Abstract: Image, graphical abstract